Gating mechanism in nicotinic acetylcholine receptor channel - Karadağ, Serkan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Nicotinic acetylcholine receptor (nAChR) is a ligand gated ion channel. Aberrations of nAChR is the primary reason of many congenital myasthenic syndromes. The mechanism behind the function of nAChRs is still unclear. In the present study nAChR from Torpedo marmorata was analyzed using the 3D structures of trasmembrane domain (TMD) (Protein Data Bank (PDB) Code: 1oed) and TMD with ligand binding domain (LBD) and five helices from the cyptoplasmic domain (PDB Code: 2bg9). Elastic Network Models (ENM), namely Gaussian Network Model (GNM) and Anisotropic Network Model (ANM), were employed to assess the underlying motions of nAChR. A program called MCPOOL was designed to analyze the correlated fluctuations by GNM to study the communication pathways between the binding domain and the gate. Conservation and correlated mutation analysis was performed to interpret the results of the ENMs from an evolutionary standpoint. The results of GNM analysis suggested that TMD domain is largely affected by LBD and cytoplasmic domain. The highly fluctuating motion of M2-M3 loop is suppressed by the presence of LBD. The cross correlations elaborated by MCPOOL revealed the pathways between binding and gating region. The most visited regions are the initial residues of M1, M2-M3 loop, and the last residues of M4. They are on the pathways and overlap the minimum fluctuating regions and highly associate with the conserved residues and the residue pairs of correlated mutations. The results agree in the suggestion that these most visited regions are key passageways on the signal transmission pathway, and thus affect the gating mechanism.
Keywords: Nicotinic receptors.; Acetylcholine -- Receptors.